An acoustic-wave preserved artificial compressibility method for low-Mach-number aeroacoustic simulations. (6th January 2022) - Jiang, Hanbo; Zhang, Xin
Abstract: An artificial compressibility (AC) method is developed for time-accurate low-Mach-number aeroacoustic simulations. The significant advantage is capturing acoustic waves in the turbulent flows at a low computational cost. An artificial equation of state with isentropic behaviour is assumed to build the relation between pressure and density fluctuations. The key measure is to rewrite the continuity equation, which is commonly expressed as ∇ ⋅ u = 0 at low Mach numbers, to a time-dependent equation for pressure. Here u is the flow velocity. Being different from the traditional AC method that was initially proposed for steady-state simulations, the present method is intended to solve transient turbulent flow at low-Mach-number conditions. Additionally, the proposed method can correctly resolve sound wave propagation, which is inherently ruled out by usual incompressible Navier–Stokes equations. Results show that the proposed method can provide fast alternatives to traditional incompressible solvers and simultaneously achieve the same time-accurate results. The capability of the proposed method is examined by benchmark aeroacoustic problems. Particularly, the challenging problem of predicting noise radiation from a propeller is considered, and the results match well with the anechoic chamber measurements.